Distinct Gut Microbiota and Metabolite Profiles Induced by Different Feeding Methods in Healthy Chinese Infants - Li, Na; Yan, Fenfen; Wang, Nana; Song, Yue; Yue, Yingxue; Guan, Jiaqi; Li, Bailiang; Huo, Guicheng (Frontiers in Microbiology, 2020)
Human milk is closely correlated with infant gut microbiota, and is important to infant development. However, most infants received insufficient exclusively breast milk and the discordance between effects of commercial formula and human milk is exist. To elucidate the differences induced by various feeding methods, we determined microbiota and metabolites composition in fecal samples from 77 healthy infants in Northeast China and identified the differences in various feeding methods. Bacterial 16S rRNA gene sequence analysis demonstrated that the fecal samples of exclusively breastfed (BF) infants were abundant in Bifidobacterium and Lactobacillus, while the mixed fed (MF) infants had the highest abundance of Veillonella and Klebsiella, the exclusively formula fed infants (FF) were enriched in Bacteroides and Blautia, the complementary food fed (CF) infants were associated with higher relative abundance of Lachnoclostridium and Akkermansia. LC-MS-based metabolomics data revealed that the fecal samples of BF infants had the highest abundance of DL-citrulline, threonine, L-proline, L-glutamine, guanine, L-arginine, whereas the MF infants were abundant in D-maltose, stearidonic acid, capric acid and myristic acid, the FF infants were enriched in itaconic acid, 4-pyridoxic acid, prostaglandin B2, thymine, DL-a-hydroxybutyric acid and orotic acid, the CF infants were associated with higher relative abundance of taurine, L-tyrosine, adenine and uric acid. Furthermore, compared to the BF infants, the MF and FF infants were more abundant in fatty acid biosynthesis. Collectively, these findings will provide probable explanations for some of the risks and benefits related to infant feeding methods, and support a theoretical basis for the development of infant formula.